To determine which of the given values \( x = -34, -12, 12 \) is a solution to the quadratic equation \( -2x^2 - 3x + 2 = 0 \), we will substitute each value into the equation and evaluate it.
Let's evaluate each value step by step:
-
For \( x = -34 \): \[ -2(-34)^2 - 3(-34) + 2 = -2(1156) + 102 + 2 \] \[ = -2312 + 102 + 2 \] \[ = -2312 + 104 = -2208 \quad (not : = 0) \]
-
For \( x = -12 \): \[ -2(-12)^2 - 3(-12) + 2 = -2(144) + 36 + 2 \] \[ = -288 + 36 + 2 \] \[ = -288 + 38 = -250 \quad (not : = 0) \]
-
For \( x = 12 \): \[ -2(12)^2 - 3(12) + 2 = -2(144) - 36 + 2 \] \[ = -288 - 36 + 2 \] \[ = -288 - 34 = -322 \quad (not : = 0) \]
Now that we have evaluated the function at all given values, we can conclude:
None of the substitutions yield 0, which means they are not solutions to the equation.
So the completed statement would be:
Only \( x = \text{none} \) is in the solution set.